2018
DOI: 10.1111/jen.12528
|View full text |Cite
|
Sign up to set email alerts
|

Improved monitoring of oriental fruit moth (Lepidoptera: Tortricidae) with terpinyl acetate plus acetic acid membrane lures

Abstract: Male and female moth catches of Grapholita molesta (Busck) in traps were evaluated in stone and pome fruit orchards untreated or treated with sex pheromones for mating disruption in Uruguay, Argentina, Chile, USA, and Italy from 2015 to 2017. Trials evaluated various blends loaded into either membrane cup lures or septa. Membrane lures were loaded with terpinyl acetate (TA), acetic acid (AA) and (Z)‐3‐hexenyl acetate alone or in combinations. Two septa lures were loaded with either the three‐component sex pher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
(87 reference statements)
3
15
0
1
Order By: Relevance
“…In both 2018 and 2019, the combination lure, Pherocon ® OFM Combo Dual, outperformed the standard sex pheromone lure. The statistically higher G. molesta captures with this dual-sex combination lure observed in our trials was consistent with our previous study, where several new experimental blends including this one were compared in field experiments in the United States, South America and Italy [ 20 ]. However, in this study, testing a commercially available lure (in which the load amount of the known compounds is protected by copyright), the female proportion was lower compared to that recorded in Mujica et al [ 20 ], where we tested similar experimental proprietary blends.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In both 2018 and 2019, the combination lure, Pherocon ® OFM Combo Dual, outperformed the standard sex pheromone lure. The statistically higher G. molesta captures with this dual-sex combination lure observed in our trials was consistent with our previous study, where several new experimental blends including this one were compared in field experiments in the United States, South America and Italy [ 20 ]. However, in this study, testing a commercially available lure (in which the load amount of the known compounds is protected by copyright), the female proportion was lower compared to that recorded in Mujica et al [ 20 ], where we tested similar experimental proprietary blends.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have shown that a combination of codling moth Cydia pomonella L. sex pheromone (( E,E )-8,10-dodecadien-1-ol, codlemone) and the three main components of the G. molesta sex pheromone (( E )-8-dodecen-1-yl-acetate, ( Z )-8-dodecen-1-yl acetate and ( Z )-8-dodecen-1-ol) enhanced G. molesta captures [ 18 ], investigating acetic acid as a synergistic compound, also [ 18 , 19 ]. Finally, in 2018, Mujica et al [ 20 ] reported a very interesting dual-sex attractiveness of several experimental combinations of the above-mentioned pheromone blends synergized by terpinyl acetate and acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Other tortricids have become more problematic following the initial adoption of MD for CM and associated reductions in broadspectrum insecticides (Knight 1995;Walker and Welter 2001). The level of female mating under MD appears to be high for CM (Knight 2006(Knight , 2007a and OBLR (Knight et al 2017), and much lower with OFM (Cichon et al 2013;Mujica et al 2018). The effectiveness of MD may also be achieved through causing a delay in mating (Knight 1997b;Vickers 1997;Fraser and Trimble 2001;Foster and Howard 1999;Jones et al 2008a).…”
Section: Mating Disruptionmentioning
confidence: 99%
“…Kairomone blends including acetic acid combined with, either pear ester or nonatriene for CM (Landolt et al 2007;Knight and Light 2012); 2-phenylethanol for OBLR and Pandemis spp. (Judd et al 2017a;Knight et al 2017); phenylacetonitrile for LBAM and eye-spotted bud moth, Spilonota ocellana (Denis and Schiffermüller) (El-Sayed et al 2016;Judd et al 2017b); and terpinyl acetate for OFM (Mujica et al 2018) have significantly increased growers' ability to monitor moths even under MD programmes. Improved phenological monitoring, including more accurate models (Knight 2007c;Joshi et al 2016), are more effectively timed with female moth catches (Knight and Light 2005c;Barros-Parada et al 2015).…”
Section: Precision Pest Managementmentioning
confidence: 99%
“…An increasing body of research has developed bisexual attractants for key tortricid pests of apple Malus domestica Borkhausen, using host plant volatiles and/or microbial‐based compounds (codling moth: Light et al., ; Landolt, Suckling, & Judd, ; Landolt et al., ; leaf rollers: Giacomuzzi et al., ; Giacomuzzi, Mattheis, Basoalto, Angeli, & Knight, ; Judd, Knight, & El‐Sayed, 2017a, 2017b; Basoalto et al., ; oriental fruit moth: Mujica et al., ). The ability of pest managers to monitor female moth populations can increase the precision in tracking the pest phenology and improve timing of control tactics (Knight & Light, 2005a).…”
Section: Introductionmentioning
confidence: 99%